2003
DOI: 10.1051/vetres:2002069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the nematophagous fungus, Duddingtonia flagrans, on the larval development of goat parasitic nematodes: a plot study

Abstract: -Effective alternatives to anthelmintic treatment against nematode parasites of goats are required because of the high prevalence of benzimidazole resistance. Towards this objective, the nematophagous fungus, Duddingtonia flagrans (Df), was used in a plot study against two main parasitic nematode species of goats, Teladorsagia circumcincta (Tcir) and Trichostrongylus colubriformis (Tcol). Worm-free, culled goats were experimentally infected with strains of Tcir and Tcol to constitute donors. Half of the animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 21 publications
2
14
1
1
Order By: Relevance
“…Previous results have demonstrated that the nematode destroying effects of fungi on Trichostrongylidae parasites in faecal cultures [1,11,19] may be reflected in reduced pasture contamination under field grazing conditions [27]. However, the results herein showed that GI nematode species were affected differently by treatment.…”
Section: Effect Of Nematophagous Fungi and Energy Supplement On Parascontrasting
confidence: 55%
“…Previous results have demonstrated that the nematode destroying effects of fungi on Trichostrongylidae parasites in faecal cultures [1,11,19] may be reflected in reduced pasture contamination under field grazing conditions [27]. However, the results herein showed that GI nematode species were affected differently by treatment.…”
Section: Effect Of Nematophagous Fungi and Energy Supplement On Parascontrasting
confidence: 55%
“…Paraud and Chartier [17] and Paraud et al [18] reported reductions higher than 80% of the larval development of Teladorsagia circumcincta or Trichostrongylus colubriformis after the administration of 5 × 10 5 chlamydospores/ kg BW/day when compared to the control. In the same way, in a plot study, after the administration of chlamydospores at a dose rate of 2.5 × 10 5 /kg BW/day to goats, Chartier and Pors [4] showed reductions in larval numbers of T. circumcincta or T. colubriformis ranging from 50 to 93% compared to the control according to the month of faecal deposit on the pasture.…”
Section: Discussionmentioning
confidence: 74%
“…In goats, preliminary studies have shown that D. flagrans is able to reduce the number of larvae in coproculture of two of the predominant nematode species in France, Teladorsagia circumcincta and Trichostrongylus colubriformis by more than 80% in experimental studies [17,18] and from 50 to 80% in a plot study [4]. Similarly, Terrill et al [23] in the southeastern United States and Chandrawathani et al [2] in Malaysia have demonstrated the capability of D. flagrans to limit the number of Haemonchus contortus infective larvae in faecal cultures in tropical conditions when varying the chlamydospore dose rates or fungal delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…This latter option is based on the administration of chlamydospores of the predacious fungus, Duddingtonia flagrans, in animal food, which leads to a reduction of the pre-parasitic stages of gastro-intestinal nematodes in the faeces as assessed in several herbivorous species (Larsen 2000). In goats, the efficacy of D. flagrans has been demonstrated against the main digestive nematode species occurring in France, Teladorsagia circumcincta and Trichostrongylus colubriformis, in experimental and in plot studies as well (Chartier and Pors 2003;Paraud and Chartier 2003;Paraud et al 2004). These results have been confirmed more recently in mixed natural infections including Haemonchus contortus species (Paraud et al 2005).…”
Section: Introductionmentioning
confidence: 99%